问题 解答题
计算(能简算的要简算)
1
2
-
1
7
×
7
10
+
5
6
(
2
3
-
5
9
×
3
8
16
7
7
18
×
1
4
+
3
4
×
7
18
45×
45
46
24×(
3
4
-
1
3
+
1
6
)
2-(
1
2
+
1
25
)-
23
50
答案

(1)

1
2
-
1
7
×
7
10
+
5
6

=

1
2
-
1
10
+
5
6

=

2
5
+
5
6

=

37
30

(2)(

2
3
-
5
9
×
3
8
)×
16
7

=(

2
3
-
5
24
)×
16
7

=

11
24
×
16
7

=

22
21

(3)

7
18
×
1
4
+
3
4
×
7
18

=(

1
4
+
3
4
)×
7
18

=1×

7
18

=

7
18

(4)45×

45
46

=(46-1)×

45
46

=46×

45
46
-1×
45
46

=45-

45
46

=44

1
46

(5)24×(

3
4
-
1
3
+
1
6
),

=24×

3
4
-24×
1
3
+24×
1
6

=18-8+4,

=14;

(6)2-(

1
2
+
1
25
)-
23
50

=2-

27
50
-
23
50

=2-(

27
50
+
23
50
),

=2-1,

=1.

选择题
单项选择题